Brain Based Learning in Civics Learning to Grow the Responsible Attitude of Elementary School Students - Linda zakiah; Adistyana Pitaloka Kusmawati; Yufiarti Yufiarti; Asep Supena (Universitas Pendidikan Ganesha, 2022)
Civics learning as education that forms attitudes and character has not been fully successful, because in learning praxis there are still many cognitive-oriented, so the problem in this study is the focus of civics learning that leads to cognitive aspects. The purpose of this study was to analyze the success of implementing the learning model used by teachers. The subjects in this study were teachers who taught elementary school students of lower grades, especially grade 3, five parents of students and twenty-five elementary school students. The research method used in this study is qualitative using a descriptive approach. The data collection technique used is by observing the participants, interviewing and using a questionnaire. The data analysis techniques used were transcription, reduction in labelling/coding, and triangulation. The results showed that the average score of student responsibility was 82.20 or as many as 88% of students who had a good attitude toward responsibility after students studied the material on Rights and Responsibilities at Home. The results of this measurement indicate that the attitude of responsibility possessed by students is one of the factors in the learning process experienced by students when the brain-based learning model is applied and used.